'We couldn't do a Prague': British government responses to loyalist strikes in Northern Ireland 1974–77. Issue 153 (May 2014) - Aveyard, Stuart C.
Abstract : In May 1974 the Ulster Workers' Council (U.W.C.), comprising loyalist trade unionists, paramilitaries and politicians, mounted a general strike backed by widespread intimidation. Their target was the Sunningdale Agreement, which produced a power-sharing executive for Northern Ireland and proposed a crossborder institution with the Republic of Ireland. After a fortnight the U.W.C. successfully brought Northern Ireland to a halt and the Executive collapsed, leading to the restoration of direct rule from Westminster. Three years later the United Unionist Action Council (U.U.A.C.) adopted the same strategy, demanding a return to devolution with majority rule and the repression of the Provisional Irish Republican Army (P.I.R.A.). This second strike was defeated. Many contemporary politicians were critical of the Labour government's failure to put down the U.W.C. strike. William Whitelaw, formerly secretary of state for Northern Ireland in Edward Heath's Conservative administration and the minister responsible for the bulk of the negotiations prior to Sunningdale, believed that the prime minister, Harold Wilson, and the new secretary of state for Northern Ireland, Merlyn Rees, did not have the same attachment to the political settlement and were less willing to support the Northern Ireland Executive in its hour of need. Paddy Devlin of the Social Democratic and Labour Party (S.D.L.P.) argued that the unwillingness to arrest those involved, 'more than any other single action by the authorities ... caused thousands of law-abiding people who had earlier given support to the executive to switch loyalties'.